REALIZING FOOD SECURITY AND POVERTY ALLEVIATION THROUGH RURAL COMMUNITY EMPOWERMENT IN RINGINKEMBAR VILLAGE MALANG REGENCY - Theresia Octastefani (The Indonesian Journal of Public Administration (IJPA), 2016)
ABSTRACT Two-thirds of Ringinkembar Village’s total population is poor people, so to meet their daily food needs are extremely difficult and limited. To solve it, one of government’s strategies is implementing Food Independent Village Program. This program focuses on the effort to empower community in order to achieve food security and alleviate poverty. The research method used was descriptive method with qualitative approach. The selection of key informants is done by purposive sampling and data was analyzed using interactive data analysis model by Miles and Huberman. The results showed that: before implementing these programs, the food security condition was proved very weak and vulnerable; after implementing these programs, the condition of food security in this village more strengthen and can develop other productive business. It can realize through the entire process of rural community empowerment that was done through four stages and successfully run by the poor household.   Keywords: Food Security, Poverty Alleviation, Rural Community Empowerment